Method and apparatus for preparing anisotropic aerogels from a dispersion of clay mineral nanoplatelets

CN121553957BActive Publication Date: 2026-10-09CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510631518.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-16
Publication Date
2026-10-09
Estimated Expiration
2045-05-16

AI Technical Summary

Technical Problem

[0004]本发明的主要目的是提供一种黏土矿物纳米片分散液制备各向异性气凝胶的方法及装置,旨在解决现有技术中,制备气凝胶的工艺复杂、成本高的技术问题

Benefits of technology

[0030] In the aforementioned method for preparing anisotropic aerogels from clay mineral nanosheet dispersions, the prepared clay mineral nanosheet dispersion is placed in a freezing mold to achieve a temperature gradient at a low temperature, and then directionally frozen under this temperature gradient. During the freezing process, the clay mineral nanosheet dispersion assembles and aligns to form solid nanosheets. Subsequently, the freezing mold and the solid nanosheets are freeze-dried together to obtain anisotropic aerogels. The directional freezing process ensures the uniform distribution and directional alignment of the solid nanosheets, improving the structural stability of the aerogel. Furthermore, the resulting aerogel exhibits excellent thermal insulation properties in the direction perpendicular to the directional alignment of the solid nanosheets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121553957B_ABST
    Figure CN121553957B_ABST
Patent Text Reader

Abstract

The application provides a method and device for preparing anisotropic aerogel from a clay mineral nanosheet dispersion liquid, comprising the following steps: placing the clay mineral nanosheet dispersion liquid in a freezing mold, and performing directional freezing to obtain solid nanosheets; and freeze-drying the freezing mold together with the solid nanosheets to obtain the anisotropic aerogel; wherein the temperature of a first end of the freezing mold is lower than the temperature of a second end, the temperature of the first end is -80 to -5 DEG C, and the freezing time is 0.5 to 8 h. A temperature gradient from the first end to the second end is formed at low temperature, and directional arrangement is performed under the temperature gradient. The formed aerogel has excellent heat insulation properties in the vertical direction of the directional arrangement of the solid nanosheets. In addition, the preparation method and device are simple in structure, convenient to operate, low in cost, and capable of realizing low-cost industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aerogel synthesis technology, and particularly relates to a method and apparatus for preparing anisotropic aerogels from clay mineral nanosheet dispersions. Background Technology

[0002] Aerogels, due to their high porosity, low density, poor gas flowability, and low thermal conductivity, possess excellent thermal insulation and lightweight properties, making them a promising candidate for high-end thermal insulation applications in aerospace, energy storage, and other fields. However, traditional aerogels (such as silica-based aerogels) rely on the sol-gel method for preparation, which involves complex processes, time-consuming procedures, and high costs. Furthermore, silica-based aerogels are brittle and fragile, with limited temperature tolerance (long-term operating temperature ≤400℃), making it difficult to meet the requirements of high-temperature extreme environments (such as spacecraft thermal protection and nuclear reactor insulation).

[0003] Clay minerals (such as muscovite), as natural layered silicate materials, possess excellent thermal stability (temperature resistance >1000℃) and low cost advantages. However, natural clay minerals typically exhibit a disordered structure, resulting in high thermal conductivity (e.g., above 0.1 W / (m·K), and their isotropic structure limits their thermal insulation performance. Based on this, this application provides a method and apparatus for preparing anisotropic aerogels from clay mineral nanosheet dispersions, yielding anisotropic clay mineral aerogels with excellent thermal insulation capabilities. Summary of the Invention

[0004] The main objective of this invention is to provide a method and apparatus for preparing anisotropic aerogels from clay mineral nanosheet dispersions, aiming to solve the technical problems of complex processes and high costs in the preparation of aerogels in the prior art.

[0005] To achieve the above objectives, the present invention provides a method for preparing anisotropic aerogels from clay mineral nanosheet dispersions, comprising the following steps:

[0006] The clay mineral nanosheet dispersion was placed in a freezing mold and directionally frozen to obtain solid nanosheets.

[0007] The anisotropic aerogel was obtained by freeze-drying the frozen mold together with the solid nanosheets.

[0008] The temperature at the first end of the freezing mold is lower than the temperature at the second end. The temperature at the first end is -80 to -5°C, and the freezing time is 0.5 to 8 hours.

[0009] According to an embodiment of this application, the directional freezing is longitudinal gradient freezing; wherein the temperature of the second end is 15-30°C.

[0010] According to the embodiments of this application, the freeze-drying temperature is -90 to -40°C, and the freeze-drying time is 12 to 48 hours.

[0011] According to an embodiment of this application, the method for preparing the clay mineral nanosheet dispersion includes:

[0012] The clay mineral raw material was subjected to calcination at a first temperature and acid activation treatment in sequence to obtain activated clay mineral.

[0013] The activated clay minerals were mixed with an organic intercalating agent and water, and the intercalation reaction was carried out under supercritical carbon dioxide conditions to obtain intercalated clay minerals.

[0014] The intercalated clay minerals are dispersed in water, ultrasonically exfoliated, and then centrifuged. The upper dispersion is collected, which is the clay mineral nanosheet dispersion.

[0015] The calcination temperature at the first temperature is 400–800°C, and the calcination time at the first temperature is 1–12 hours.

[0016] According to an embodiment of this application, the method for preparing the clay mineral nanosheet dispersion includes:

[0017] The clay mineral raw material is mixed with the intercalating agent and then calcined at a second temperature to obtain a solid substance, which is the intercalated clay mineral.

[0018] Intercalated clay minerals are dispersed in water, homogenized, ultrasonically exfoliated, and then centrifuged. The upper dispersion is collected, which is the clay mineral nanosheet dispersion.

[0019] The mass ratio of clay mineral raw material to intercalating agent is 1:1 to 1:20; the second calcination temperature is 250 to 850°C, and the calcination time is 1 to 24 hours.

[0020] According to embodiments of this application, the intercalating agent includes one or more of sodium chloride, sodium nitrate, lithium chloride, lithium nitrate, magnesium chloride, zinc chloride, zinc nitrate, copper chloride, and copper nitrate.

[0021] According to an embodiment of this application, the mass ratio of the intercalated clay mineral to water is 1:2 to 1:50.

[0022] According to the embodiments of this application, the homogenization speed is 10,000 to 20,000 rpm, and the homogenization time is 10 to 720 min.

[0023] According to the embodiments of this application, the power of the ultrasound is 100-3000W, and the ultrasound time is 10-720min; the centrifugation speed is 500-4000rpm, and the centrifugation time is 5-20min.

[0024] This invention also provides an apparatus for preparing anisotropic aerogels from clay mineral nanosheet dispersions, comprising:

[0025] The freezing mold includes a cavity formed by a first end, a second end, and a sidewall; the first end is a metal with high thermal conductivity, and the sidewall is a non-metal with low thermal conductivity; the first end and the sidewall form a thermal barrier interface through a sealing structure, which is used to directionally freeze the prepared clay mineral nanosheet dispersion to obtain solid nanosheets.

[0026] The cryogenic reactor comes into contact with the first end of the cryogenic mold, forming a temperature gradient from the first end to the second end. The cryogenic mold and solid nanosheets are freeze-dried together to obtain anisotropic aerogel.

[0027] The temperature of the first end of the freezing mold is -80 to -5°C, and the freezing time is 0.5 to 8 hours.

[0028] The freeze-drying temperature is -90 to -40°C, and the freeze-drying time is 12 to 48 hours.

[0029] The beneficial effects of this invention are:

[0030] In the aforementioned method for preparing anisotropic aerogels from clay mineral nanosheet dispersions, the prepared clay mineral nanosheet dispersion is placed in a freezing mold to achieve a temperature gradient at a low temperature, and then directionally frozen under this temperature gradient. During the freezing process, the clay mineral nanosheet dispersion assembles and aligns to form solid nanosheets. Subsequently, the freezing mold and the solid nanosheets are freeze-dried together to obtain anisotropic aerogels. The directional freezing process ensures the uniform distribution and directional alignment of the solid nanosheets, improving the structural stability of the aerogel. Furthermore, the resulting aerogel exhibits excellent thermal insulation properties in the direction perpendicular to the directional alignment of the solid nanosheets.

[0031] In addition, the preparation method and apparatus of the present invention are simple to set up, easy to operate, low in cost, and can achieve low-cost industrial production. Attached Figure Description

[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0033] Figure 1 Image of a freezing mold;

[0034] Figure 2SEM image of the prepared anisotropic aerogel in the longitudinal parallel direction;

[0035] Figure 3 SEM images of the anisotropic aerogel at different magnifications in the longitudinal direction; where (a) is magnified 30 times and (b) is magnified 100 times.

[0036] Figure 4 SEM images of isotropic aerogels at different magnifications in the longitudinal direction perpendicular to the aerogel; where (a) is magnified 30 times and (b) is magnified 100 times.

[0037] Figure 5 The heat insulation effect of the prepared anisotropic aerogel during high-temperature combustion heat insulation test from 0 to 40 s is shown in the figure; where (a) 0 s, (b) 5 s, (c) 10 s, (d) 40 s.

[0038] Figure 6 The graph shows the relationship between the thermal conductivity of anisotropic aerogels prepared with different concentrations of mica nanosheet dispersions.

[0039] The realization of the objective, functional characteristics and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0040] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0041] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0042] To achieve the above objectives, the present invention provides a method for preparing anisotropic aerogels from clay mineral nanosheet dispersions, comprising the following steps:

[0043] The clay mineral nanosheet dispersion was placed in a freezing mold and directionally frozen to obtain solid nanosheets.

[0044] The temperature at the first end of the freezing mold is lower than the temperature at the second end. The temperature at the first end is -80 to -5°C, and the freezing time is 0.5 to 8 hours.

[0045] In some embodiments, a clay mineral nanosheet dispersion is placed in a freezing mold. The freezing mold has a first end and a second end arranged opposite each other. The first end of the freezing mold is made of a metal material with high thermal conductivity, such as copper. The sidewalls are made of a non-metal with low thermal conductivity, such as polytetrafluoroethylene (PTFE). The first end and the sidewalls form a thermal barrier interface through a sealing structure, which is used to directionally freeze the clay mineral nanosheet dispersion placed in the freezing mold at a low temperature. For example, a cryogenic reactor is used, and the first end of the freezing mold contacts the cryogenic reactor, forming a temperature gradient from the first end to the second end, thus directionally freezing the clay mineral nanosheet dispersion to obtain solid nanosheets. This ensures the uniform distribution and directional arrangement of the solid nanosheets, improving the structural stability of the anisotropic aerogel.

[0046] In some embodiments, the frozen mold and solid nanosheets are freeze-dried together, and after removing the ice crystals using a freeze dryer, the anisotropic aerogel is obtained.

[0047] In some embodiments, the freezing mold can be placed in multiple ways. For example, it can be placed vertically from the first end to the second end, meaning the temperature gradient from the first end to the second end is in the vertical direction, and the corresponding directional freezing method is longitudinal gradient freezing. Or, it can be placed horizontally from the first end to the second end, meaning the temperature gradient from the first end to the second end is in the horizontal direction, and the corresponding directional freezing method is horizontal gradient freezing.

[0048] For ease of description, the following description will use the vertical direction as an example. Accordingly, the first end is located at the bottom and has a low temperature, while the second end is located at the top and has a high temperature, forming a temperature gradient from bottom to top (i.e., vertical) to achieve directional freezing of the clay mineral nanosheet dispersion.

[0049] In some embodiments, the directional freezing is longitudinal gradient freezing; wherein the temperature of the second end is 15–30°C. This achieves the formation of a longitudinal temperature gradient at low temperatures, and allows for directional freezing and alignment within this temperature gradient. Clay mineral nanosheets assemble and align themselves during the longitudinal freezing process, forming solid nanosheets.

[0050] In some embodiments, the freeze-drying temperature is -90 to -40°C, and the freeze-drying time is 12 to 48 hours. Ice crystals can be further removed while retaining the oriented arrangement of the solid nanosheets to obtain anisotropic aerogels.

[0051] In the aforementioned method for preparing anisotropic aerogels from clay mineral nanosheet dispersions, the clay mineral nanosheet dispersion is placed in a freezing mold to create a temperature gradient between the first and second ends at low temperatures, and then directional freezing is performed under this temperature gradient. During the freezing process, the clay mineral nanosheet dispersion assembles and aligns to form solid nanosheets. Subsequently, the freezing mold and the solid nanosheets are freeze-dried together to obtain the anisotropic aerogel. The directional freezing process ensures the uniform distribution and directional alignment of the solid nanosheets, improving the structural stability of the aerogel. Furthermore, it exhibits excellent thermal insulation properties in the direction perpendicular to the directional alignment of the solid nanosheets.

[0052] Moreover, the preparation method of the present invention is simple, easy to operate, and can achieve low-cost industrial production.

[0053] In some embodiments, the method for preparing the clay mineral nanosheet dispersion includes:

[0054] The clay mineral raw material was subjected to calcination at a first temperature and acid activation treatment in sequence to obtain activated clay mineral.

[0055] In some embodiments, the clay mineral raw material is calcined at a first temperature in an air atmosphere, such as using a muffle furnace. The first calcination temperature is 400–800°C, and the calcination time is 1–12 hours to ensure sufficient activation. It is then mixed with acid for further activation treatment to obtain activated clay minerals. This can further alter the surface properties and chemical structure of the clay minerals, making their microstructure relatively rough, increasing their specific surface area, and thus improving their reactivity. The particle size of the clay mineral raw material is less than 200 mesh, such as when the clay mineral raw material is in powder form.

[0056] In some embodiments, the acid activation treatment step includes: calcining the clay mineral raw material at a first temperature, mixing it evenly with an acid, and heating it to obtain activated clay minerals. The acid includes one or more of hydrochloric acid, sulfuric acid, and nitric acid. The concentration of the acid is 1–5 mol / L. The mass ratio of the clay mineral powder to the acid is 1:1 to 1:10. The heating temperature is 60–120°C, and the heating time is 1–12 hours.

[0057] The activated clay minerals were mixed with an organic intercalating agent and water, and the intercalation reaction was carried out under supercritical carbon dioxide conditions to obtain intercalated clay minerals.

[0058] In some embodiments, a supercritical carbon dioxide apparatus is used to uniformly mix activated clay minerals, an organic intercalating agent, and water, and then carry out an intercalation reaction under supercritical carbon dioxide conditions to obtain intercalated clay minerals. Because supercritical carbon dioxide has low viscosity and high permeability, the organic intercalating agent can effectively enter the interlayer region of the activated clay minerals and weaken the interlayer forces of the activated clay minerals.

[0059] The supercritical carbon dioxide conditions include reaction temperature, reaction pressure, and reaction time. The reaction temperature is 25–90℃, the reaction pressure is 7–20 MPa, and the reaction time is 1–24 h. The mass ratio of the organic intercalating agent to the activated clay mineral is 0.2:1–4:1, and the mass ratio of the mixture of the organic intercalating agent and the activated clay mineral to water is 1:5–1:30. The organic intercalating agent includes one or more of hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, and decadecyltrimethylammonium bromide.

[0060] The intercalated clay minerals are dispersed in water, ultrasonically exfoliated, and then centrifuged. The upper dispersion is collected, which is the clay mineral nanosheet dispersion.

[0061] The calcination temperature at the first temperature is 400–800°C, and the calcination time at the first temperature is 1–12 hours.

[0062] In some embodiments, the intercalated clay minerals are mixed with deionized water to form a homogeneous suspension. An ultrasonic processor is then used to sonicate the suspension. The ultrasonic exfoliation power is 200–1000 W, and the sonication time is 10–120 min. Afterwards, centrifugation is performed, and the supernatant dispersion is collected, which is the clay mineral nanosheet dispersion.

[0063] In some embodiments, the method for preparing the clay mineral nanosheet dispersion includes:

[0064] The clay mineral raw material is mixed with an intercalating agent and then calcined at a second temperature to obtain a solid substance, which is the intercalated clay mineral. The mass ratio of the clay mineral raw material to the intercalating agent is 1:1 to 1:20; the second calcination temperature is 250 to 850°C, and the calcination time is 1 to 24 hours.

[0065] In some embodiments, the clay mineral raw material and the intercalating agent are mixed uniformly in a solid state, placed in a corundum crucible, and heated in a muffle furnace under an air atmosphere. After calcination at a second temperature, the resulting solid substance is the intercalated clay mineral. Under heating conditions, the intercalating agent can undergo ion exchange with the clay mineral raw material, thereby increasing the interlayer spacing.

[0066] In some embodiments, the clay minerals include one or more of talc, serpentine, montmorillonite, illite, vermiculite, muscovite, phlogopite, biotite, and sericite.

[0067] In some embodiments, the intercalating agent includes one or more of sodium chloride, sodium nitrate, lithium chloride, lithium nitrate, magnesium chloride, zinc chloride, zinc nitrate, copper chloride, and copper nitrate.

[0068] Intercalated clay minerals are dispersed in water, homogenized, ultrasonically exfoliated, and then centrifuged. The upper dispersion is collected, which is the clay mineral nanosheet dispersion.

[0069] In some embodiments, intercalated clay minerals are dispersed in water, homogenized using a high-speed homogenizer, and subjected to high-power ultrasonication to enhance the exfoliation of the intercalated clay minerals. After exfoliation, centrifugation is performed to separate the exfoliated clay mineral nanosheets into single-layer or few-layer structures from the unexfoliated clay mineral powder. The upper dispersion is collected to obtain a highly stable clay mineral nanosheet dispersion.

[0070] In some embodiments, the mass ratio of the intercalated clay mineral to water is 1:2 to 1:50.

[0071] In some embodiments of this application, the homogenization speed is 10,000 to 20,000 rpm, and the homogenization time is 10 to 720 min.

[0072] In some embodiments, the ultrasonic power is 100-3000W, the ultrasonic time is 10-720min, the centrifugation speed is 500-4000rpm, and the centrifugation time is 5-20min.

[0073] This invention also provides an apparatus for preparing anisotropic aerogels from clay mineral nanosheet dispersions, comprising:

[0074] The freezing mold includes a cavity formed by a first end, a second end, and a sidewall; the first end is made of a metal with high thermal conductivity, and the sidewall is made of a non-metal with low thermal conductivity; the first end and the sidewall form a thermal barrier interface through a sealing structure, used for the directional freezing of the prepared clay mineral nanosheet dispersion to obtain solid nanosheets. The temperature of the first end of the freezing mold is -80 to -5°C, and the freezing time is 0.5 to 8 hours.

[0075] In some embodiments, the first end of the freezing mold is a metal with high thermal conductivity, such as copper. The sidewalls are non-metals with low thermal conductivity, such as polytetrafluoroethylene (PTFE). The first end and the sidewalls form a thermal barrier interface through a sealing structure, which is used to directionally freeze the clay mineral nanosheet dispersion at low temperatures.

[0076] A cryogenic reactor is brought into contact with the first end of the cryogenic mold, forming a temperature gradient from the first end to the second end. The cryogenic mold and solid nanosheets are then freeze-dried together to obtain anisotropic aerogel. The freeze-drying temperature is -90 to -40°C, and the freeze-drying time is 12 to 48 hours.

[0077] In some embodiments, during directional freezing at low temperatures, the cryogenic reactor only contacts the first end of the freezing mold, while the temperature of the second end of the freezing mold is 15–30°C. This creates a temperature gradient from the first to the second end of the freezing mold at low temperatures, and the solid nanosheets are freeze-oriented under this temperature gradient to obtain solid nanosheets. The freezing mold and the solid nanosheets are then freeze-dried together to obtain anisotropic aerogels. These aerogels exhibit excellent thermal insulation properties in the direction perpendicular to the directional alignment of the solid nanosheets.

[0078] The apparatus for preparing anisotropic aerogels from clay mineral nanosheet dispersions of the present invention is simple in design and easy to operate. It not only improves the efficiency of testing and production but also reduces costs.

[0079] To further illustrate the present invention, the following examples are provided:

[0080] In the embodiments and comparative examples of this invention, the clay mineral used is raw mica ore mined from Shangrao City, Jiangxi Province, China, and its main component is muscovite (KAl2[AlSi3O4)). 10 [OH]2), specifically, the content of other impurities is less than 2 wt%. The intercalating agent used is lithium nitrate, purchased from Maclean Company, China. The microstructure of the aerogel was characterized by field emission scanning electron microscopy.

[0081] Example 1

[0082] Mica powder was calcined at 750℃ in air for 5 hours and then mixed with 5 mol / L nitric acid at a mass ratio of 1:6 in a three-necked flask. The mixture was then placed in a heating mantle and heated at 95℃ for 5 hours to obtain activated mica powder. The activated mica powder, hexadecyltrimethylammonium bromide, and water were then mixed, with the mass ratio of activated mica powder to hexadecyltrimethylammonium bromide being 1:3 and the mass ratio of the mixture of activated mica powder, hexadecyltrimethylammonium bromide, and water being 1:25. An intercalation reaction was carried out in a supercritical carbon dioxide apparatus. The reaction temperature was 40℃, the reaction pressure was 18 MPa, and the reaction time was 12 hours to obtain intercalated mica powder. The intercalated mica powder was dispersed in water and ultrasonically exfoliated at 400W for 30 minutes. After centrifugation at 1000 rpm, the supernatant dispersion was collected to obtain a highly stable mica nanosheet dispersion.

[0083] The mica nanosheet dispersion was prepared with a concentration of 20 g / L. The mica nanosheet dispersion was placed in a freezing mold with the temperature of the first end of the freezing mold at -20°C. The mixture was then directionally frozen for 2 hours to obtain solid nanosheets. The freezing mold and the solid nanosheets were then freeze-dried together at -50°C for 48 hours to obtain anisotropic aerogel.

[0084] Example 2

[0085] Mica powder and an intercalating agent were mixed in a solid state, with a mass ratio of mica powder to intercalating agent of 17:1. The mixture was then calcined at 350°C in air for 12 hours to obtain intercalated mica. The intercalated mica was dispersed in water, homogenized at 10,000 rpm for 30 minutes, sonicated at 400 W for 30 minutes, and then centrifuged to collect the supernatant, yielding a highly stable mica nanosheet dispersion.

[0086] A mica nanosheet dispersion with a concentration of 30 g / L was placed in a freezing mold. The temperature of the first end of the freezing mold was -20°C. The mixture was then directionally frozen for 2 hours to obtain solid nanosheets. The freezing mold and the solid nanosheets were then freeze-dried together at -50°C for 48 hours to obtain anisotropic aerogel.

[0087] Example 3

[0088] Mica powder and an intercalating agent were mixed in a solid state, with a mass ratio of mica powder to intercalating agent of 17:1. The mixture was then calcined at 350°C in air for 12 hours to obtain intercalated mica. The intercalated mica was dispersed in water, homogenized at 10,000 rpm for 30 minutes, sonicated at 400 W for 30 minutes, and then centrifuged to collect the supernatant, yielding a highly stable mica nanosheet dispersion.

[0089] A mica nanosheet dispersion with a concentration of 20 g / L was placed in a freezing mold. The temperature of the first end of the freezing mold was -20°C. The mixture was directionally frozen for 2 hours to obtain solid nanosheets. The freezing mold and the solid nanosheets were then freeze-dried together at -50°C for 48 hours to obtain anisotropic aerogel.

[0090] Example 4

[0091] Mica powder and an intercalating agent were mixed in a solid state, with a mass ratio of mica powder to intercalating agent of 17:1. The mixture was then calcined at 350°C in air for 12 hours to obtain intercalated mica. The intercalated mica was dispersed in water, homogenized at 10,000 rpm for 30 minutes, sonicated at 400 W for 30 minutes, and then centrifuged to collect the supernatant, yielding a highly stable mica nanosheet dispersion.

[0092] A mica nanosheet dispersion with a concentration of 40 g / L was placed in a freezing mold. The temperature of the first end of the freezing mold was -20°C. The mixture was then directionally frozen for 2 hours to obtain solid nanosheets. The freezing mold and the solid nanosheets were then freeze-dried together at -50°C for 48 hours to obtain anisotropic aerogel.

[0093] Example 5

[0094] Mica powder and an intercalating agent were mixed in a solid state, with a mass ratio of mica powder to intercalating agent of 17:1. The mixture was then calcined at 350°C in air for 12 hours to obtain intercalated mica. The intercalated mica was dispersed in water, homogenized at 10,000 rpm for 30 minutes, sonicated at 400 W for 30 minutes, and then centrifuged to collect the supernatant, yielding a highly stable mica nanosheet dispersion.

[0095] A mica nanosheet dispersion with a concentration of 50 g / L was placed in a freezing mold. The temperature of the first end of the freezing mold was -20°C. The mixture was then directionally frozen for 2 hours to obtain solid nanosheets. The freezing mold and the solid nanosheets were then freeze-dried together at -50°C for 48 hours to obtain anisotropic aerogel.

[0096] Comparative Example 1

[0097] Mica powder and an intercalating agent were mixed in a solid state, with a mass ratio of mica powder to intercalating agent of 17:1. The mixture was then calcined at 350°C in air for 12 hours to obtain intercalated mica. The intercalated mica was dispersed in water, homogenized at 10,000 rpm for 30 minutes, sonicated at 400 W for 30 minutes, and then centrifuged to collect the supernatant, yielding a highly stable mica nanosheet dispersion.

[0098] A mica nanosheet dispersion with a concentration of 20 g / L was placed in a common polytetrafluoroethylene mold and frozen at -20°C for 2 h to obtain a solidified dispersion. The solidified dispersion, together with the common polytetrafluoroethylene mold, was freeze-dried at -50°C for 48 h to obtain an isotropic aerogel.

[0099] in, Figure 1 This is a diagram of the freezing mold of the present invention; Figure 2 SEM image of the prepared anisotropic aerogel in the longitudinal parallel direction; Figure 3 SEM images of the prepared anisotropic aerogel at different magnifications in the longitudinal direction perpendicular to the direction of the longitudinal direction; Figure 3 (a) Magnified 30 times, Figure 3 (b) Magnified 100 times; Figure 4 SEM images of isotropic aerogels at different magnifications in the longitudinal direction perpendicular to the direction of the longitudinal direction; Figure 4 (a) Magnified 30 times, Figure 4 (b) Magnified 100 times; Figure 5 The graph shows the thermal insulation effect of the prepared anisotropic aerogel during high-temperature combustion thermal insulation testing from 0 to 40 seconds. Figure 5 (a) represents high-temperature combustion for 0 seconds. Figure 5 (b) is high-temperature combustion for 5 seconds. Figure 5 (c) represents high-temperature combustion for 10 seconds. Figure 5 (d) represents high-temperature combustion for 40 seconds; Figure 6The graph shows the relationship between the thermal conductivity of anisotropic aerogels prepared with different concentrations of mica nanosheet dispersions.

[0100] from Figure 1 As can be seen, by placing the mica nanosheet dispersion in the middle groove of the freezing mold, combined with the method of preparing anisotropic aerogels from the clay mineral nanosheet dispersion of the present invention, a longitudinal temperature gradient is preferentially formed at the first end, that is, the temperature gradient from the first end to the second end of the freezing mold, and directional freezing is performed under this temperature gradient to obtain solid nanosheets.

[0101] from Figure 2 It can be seen that the anisotropic aerogels obtained in Examples 1-5 were characterized by SEM in the longitudinal parallel direction. Figure 2 The aerogels exhibit a complete, assembled, large-scale layered structure. Furthermore, the anisotropic aerogels obtained in Examples 1-5 were characterized using SEM in the longitudinal vertical direction, as shown... Figure 3 As shown, it exhibits a distinct layered, uniformly distributed structure, with the layers connected by nanosheets to form a relatively stable framework structure. The isotropic aerogel obtained in Comparative Example 1 was characterized using SEM in the longitudinal direction, as shown... Figure 4 As shown, it exhibits a clearly chaotic layered structure.

[0102] The anisotropic aerogels obtained in Examples 1-5 were subjected to combustion insulation tests at a temperature of 500°C. Figure 5 As shown, continuous heating within 0–40 seconds did not affect the flammable organic polymer placed on the anisotropic aerogel, indicating that the anisotropic aerogel has excellent thermal insulation properties.

[0103] from Figure 6 It can be seen that the thermal conductivity of the aerogel varies with different concentrations of mica nanosheet dispersion. Lowering the thermal conductivity improves the thermal insulation performance. The optimal thermal insulation effect is observed when the mica nanosheet dispersion concentration is 30 g / L, with an aerogel thermal conductivity of 0.039 W / (m·K).

[0104] In summary, this invention involves placing a mica nanosheet dispersion into a freezing mold at -20°C for 2 hours to obtain solid nanosheets. The freezing mold and solid nanosheets are then freeze-dried together at -50°C for 48 hours to obtain anisotropic aerogels. The optimal thermal insulation effect is achieved when the mica nanosheet dispersion concentration is 30 g / L. The apparatus for preparing anisotropic aerogels from clay mineral nanosheet dispersions is simple in design and easy to operate. This not only improves the efficiency of testing and production but also reduces costs.

[0105] In summary, the above-described technical solutions of the present invention are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. All equivalent structural transformations made using the contents of the present invention's specification and drawings under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A method for preparing anisotropic aerogels from a clay mineral nanosheet dispersion, characterized in that, Includes the following steps: The clay mineral nanosheet dispersion was placed in a freezing mold and directionally frozen to obtain solid nanosheets; The anisotropic aerogel was obtained by freeze-drying the frozen mold together with the solid nanosheets. The temperature at the first end of the freezing mold is lower than the temperature at the second end, the temperature at the first end is -80~-5℃, and the freezing time is 0.5~8h; The directional freezing is longitudinal gradient freezing; The temperature at the second end is 15~30℃; The method for preparing the clay mineral nanosheet dispersion includes: S1: The clay mineral raw material is sequentially subjected to calcination at the first temperature and acid activation treatment to obtain activated clay mineral; S2: The activated clay minerals are mixed with an organic intercalating agent and water, and the intercalation reaction is carried out under supercritical carbon dioxide conditions to obtain intercalated clay minerals. S3: Disperse the intercalated clay minerals in water, exfoliate them by ultrasonication, centrifuge them, and collect the upper dispersion, which is the clay mineral nanosheet dispersion. The calcination temperature at the first temperature is 400~800℃, and the calcination time at the first temperature is 1~12h; The clay mineral nanosheet dispersion is a mica nanosheet dispersion.

2. The method for preparing anisotropic aerogels from clay mineral nanosheet dispersions according to claim 1, characterized in that, The freeze-drying temperature is -90 to -40°C, and the freeze-drying time is 12 to 48 hours.

3. A method for preparing anisotropic aerogels from a clay mineral nanosheet dispersion, characterized in that, Includes the following steps: The clay mineral nanosheet dispersion was placed in a freezing mold and directionally frozen to obtain solid nanosheets; The anisotropic aerogel was obtained by freeze-drying the frozen mold together with the solid nanosheets. The temperature at the first end of the freezing mold is lower than the temperature at the second end, the temperature at the first end is -80~-5℃, and the freezing time is 0.5~8h; The directional freezing is longitudinal gradient freezing; The temperature at the second end is 15~30℃; The method for preparing the clay mineral nanosheet dispersion includes: S1: Mix clay mineral raw materials with intercalating agent, and calcine at a second temperature to obtain solid material, which is intercalated clay mineral; S2: Disperse the intercalated clay minerals in water, homogenize, ultrasonically exfoliate, and centrifuge to collect the upper dispersion, which is the clay mineral nanosheet dispersion. The mass ratio of clay mineral raw material to intercalating agent is 1:1 to 1:20; the second calcination temperature is 250 to 850°C, and the calcination time is 1 to 24 hours.

4. The method for preparing anisotropic aerogels from clay mineral nanosheet dispersions according to claim 3, characterized in that, The intercalating agent includes one or more of sodium chloride, sodium nitrate, lithium chloride, lithium nitrate, magnesium chloride, zinc chloride, zinc nitrate, copper chloride, and copper nitrate.

5. The method for preparing anisotropic aerogels from clay mineral nanosheet dispersions according to claim 3, characterized in that, The mass ratio of the intercalated clay mineral to water is 1:2 to 1:

50.

6. The method for preparing anisotropic aerogels from clay mineral nanosheet dispersions according to claim 3, characterized in that, The homogenization speed is 10,000 to 20,000 rpm, and the homogenization time is 10 to 720 min.

7. The method for preparing anisotropic aerogels from clay mineral nanosheet dispersions according to claim 3, characterized in that, The ultrasonic power is 100~3000W, and the ultrasonic time is 10~720min; the centrifugation speed is 500~4000rpm, and the centrifugation time is 5~20min.

Citation Information

Patent Citations

  • Method for preparing anisotropic cellulose-based aerogel

    CN110396214A

  • Ionic cross-linked clay aerogel material as well as preparation method and application thereof

    CN113769669A

  • Ionic liquid modified mica nanosheet as well as preparation method and application thereof

    CN116477636A